2021
DOI: 10.3390/ijms22189999
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Delivery of RGD-Containing Osteopontin Heptamer Peptide Confers Neuroprotection in the Ischemic Brain and Augments Microglia M2 Polarization

Abstract: Osteopontin (OPN), a phosphorylated glycoprotein, is induced in response to tissue damage and inflammation in various organs, including the brain. In our previous studies, we reported the robust neuroprotective effects of the icosamer OPN peptide OPNpt20, containing arginine-glycine-aspartic acid (RGD) and serine-leucine-alanine-tyrosine (SLAY) motifs, in an animal model of transient focal ischemia and demonstrated that its anti-inflammatory, pro-angiogenic, and phagocytosis inducing functions are responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…During stroke-like episodes in patients with mitochondrial disease, transient changes and fading were observed in brain magnetic resonance imaging (MRI) within 1 week of arginine administration [ 44 ]. Bone bridge protein peptides containing arginine, alanine, and aspartate motifs significantly reduced brain infarct volume in the MCAO model [ 45 ]. Mitaki et al showed that histidine-rich glycoprotein was significantly upregulated in future IS patients, which also provided a possible biomarker for predicting or targeting treatment of IS [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…During stroke-like episodes in patients with mitochondrial disease, transient changes and fading were observed in brain magnetic resonance imaging (MRI) within 1 week of arginine administration [ 44 ]. Bone bridge protein peptides containing arginine, alanine, and aspartate motifs significantly reduced brain infarct volume in the MCAO model [ 45 ]. Mitaki et al showed that histidine-rich glycoprotein was significantly upregulated in future IS patients, which also provided a possible biomarker for predicting or targeting treatment of IS [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of ischemia, intranasal delivery of an OPN/SPP1 seven‐amino acid peptide confers protection against ischemia. The heptamer peptide downregulates the expression of IL‐1β, IL‐6, and TNF‐α 78 through a putative mechanism involving αvβ3 integrin 79 . A very recent elegant study delineated a mechanism between T‐regulatory cells expressing OPN/SPP1 that infiltrate the brain after chronic stroke injury and engage integrin‐β1 expressed specifically on microglia to stimulate the proliferation and differentiation of new oligodendrocytes having the capacity to remyelinate the injured brain 80 .…”
Section: A Sensor Of Cns Injury and Inducer Of Neuroprotective Signalingmentioning
confidence: 99%
“…However, ventricular injection of osteopontin reduced the secondary neurodegeneration of the thalamus after cortical stroke [53], consistent with osteopontin being neuroprotective. On the other hand, small peptides containing the RGD integrin-binding motif of osteopontin were protective in transient MCAO models [66,87], suggesting these peptides block integrin receptors that are mediating pathological phagocytosis or neuroinflammation.…”
Section: Evidence That Microglial Activation and Phagocytosis Are Ben...mentioning
confidence: 99%
“…The latter finding suggests that phagocytosis by both microglia and astrocytes can be detrimental in ischemic stroke. The phagocytic vitronectin receptor (α v β 3 ) can be blocked with RGD-containing peptides, and the nasal delivery of these peptides provides substantial protection in rat models of ischemic stroke [66,87]. Hence, more research and clinical trials targeting microglial phagocytosis are likely to be of benefit in stroke medicine.…”
Section: Strokementioning
confidence: 99%